1997
DOI: 10.1192/bjp.171.1.69
|View full text |Cite
|
Sign up to set email alerts
|

Family planning needs and STD risk behaviours of female psychiatric out-patients

Abstract: These results underscore the priority for developing programmes that reduce female psychiatric patients' risk for unwanted pregnancies and STDs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
66
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(67 citation statements)
references
References 11 publications
1
66
0
Order By: Relevance
“…They may also be at increased risk of developing a sexually transmitted disease, more specifically having less knowledge of AIDS (Aruffo et al, 1990;Coverdale et al, 1997). …”
Section: Women's Physical Healthmentioning
confidence: 99%
“…They may also be at increased risk of developing a sexually transmitted disease, more specifically having less knowledge of AIDS (Aruffo et al, 1990;Coverdale et al, 1997). …”
Section: Women's Physical Healthmentioning
confidence: 99%
“…Yet patients with major mental disorders, including schizophrenia-spectrum disorders, may have an enhanced risk when compared to groups of patients without mental disorders for both unwanted pregnancies and children given up for others to raise [8,9]. Although the literature is scant on the family planning needs of patients with major mental disorders, one review found that many women with schizophrenia had multiple partners, high rates of coerced or forced sex, high rates of HIV risk behaviors, and limited knowledge about sexuality [10].…”
Section: Family Planning Needs Of Patients With Major Mental Disordersmentioning
confidence: 99%
“…Although the literature is scant on the family planning needs of patients with major mental disorders, one review found that many women with schizophrenia had multiple partners, high rates of coerced or forced sex, high rates of HIV risk behaviors, and limited knowledge about sexuality [10]. Even when many heterosexually active women with major mental disorders do not want to become pregnant, they may not use birth control consistently, if at all [9,11]. Alcohol or illicit substance use disorders, which are likely more common in those with major mental disorders [12,13], may contribute to the risk for unwanted pregnancies and the adverse consequences of those pregnancies.…”
Section: Family Planning Needs Of Patients With Major Mental Disordersmentioning
confidence: 99%
See 1 more Smart Citation
“…Fifty per cent of women with schizophrenia and 10% of women with affective disorder in a mother and baby unit were discharged without their child . Another study reported that 60% of children born to 80 female patients with chronic psychiatric disorders were reared by others, most commonly the child's father or an adoptive family (Coverdale & Aruffo, 1989). It is not clear to what extent mothers with mental disorders retain responsibilities for their children (Mowbray et al, 1995) and the incidence, in unbiased samples, of mothers with mental illness not caring for their children is not known.…”
Section: Impact On Patients With a Psychotic Disorder Of Having Childrenmentioning
confidence: 99%